Investigation of Fiber Optical Parametric Amplifier Performance in DWDM Transmission Systems - Olonkins, S.; Bobrovs, V.; Ivanovs, G. (Elektronika ir Elektrotechnika, 2014)
During the last decade, due to the growing demand on high capacity transmission, the evolution of optical transmission systems is moving into the focus of dense and cost-effective solutions. This has resulted in stricter requirements for the elements used in optical transmission systems, including optical amplifiers (FOPAs). One of the innovative and most promising types of amplifiers is fiber optical parametric amplifiers. In this article the authors implement a lumped single pump FOPA in a 8 channel DWDM transmission system and investigate the performance of the FOPA in order to obtain a configuration that would ensure higher level of amplification coped with less amplifier produced signal impairments. DOI: http://dx.doi.org/10.5755/j01.eee.20.1.6170